The microstress effect : how little things pile up and create big problems--and what to do about it - Cross, Robert L., 1967-; Dillon, Karen; Dillon, Karen (Editor) (Ascent Audio, 2023)
There is a force in our everyday lives that we aren't even aware of-and it's so powerful it threatens to derail otherwise promising careers and lives: microstress. It's the hidden epidemic of small moments of anxiety that infiltrate both our work and personal lives. Because each individual microstress is so small, it doesn't trigger the normal stress response in our brains to help us deal with it. Instead, the microstress just embeds in our minds, accumulating along with scores of other microstresses, day-to-day and week-to-week. The long-term effect is devastating: microstress invisibly weighs us down, damages our physical and emotional health, and contributes to a decline in our overall well-being. The good news is that once you learn about microstress, you can fight back. Drawing on fresh research, Rob Cross and Karen Dillon will teach you how to recognize and manage the most common forms of microstress, and even remove some from your life. Compelling interviews with high achievers who've endured their share of microstress bring to life best practices that show you how to build resilience against microstress, and ultimately how to find purpose in your everyday life, using it as an antidote to your own microstress.